Annual operating characteristics analysis of photovoltaic-energy storage microgrid based on retired lithium iron phosphate batteries. (January 2022) - Gao, Yan; Cai, Yingling; Liu, Chenglin
Highlights: Retired lithium iron phosphate batteries are reused in microgrid. Retired batteries in year-round operation have stable status and good performance. Using retired batteries can reduce the cost of energy storage in microgrid. Photovoltaic-energy storage microgrid have economic and environmental benefits. This project has a long payback period, with an expected cost recovery of 11 years. Abstract: A large number of lithium iron phosphate (LiFePO4 ) batteries are retired from electric vehicles every year. The remaining capacity of these retired batteries can still be used. Therefore, this paper applies 17 retired LiFePO4 batteries to the microgrid, and designs a grid-connected photovoltaic-energy storage microgrid (PV-ESM). PV-ESM was built in office buildings in Shanghai, and its operating performance was studied through experiments. After one year of operation, the analysis is carried out from four aspects: retired batteries operating characteristics, combined PV-batteries operating characteristics, electric energy flow conditions and annual operating benefits. The results show that 17 retired batteries can maintain capacity consistency, voltage consistency and temperature consistency throughout the year. The maximum capacity attenuation is 4.95Ah, and the minimum is 1.65Ah. The average annual energy efficiency of the retired battery bank is 96.16%. The monthly average proportion of combined PV-batteries energy supply in the load demand is 40%. The performance of the selected retired LiFePO4 battery can meet the energy storage requirements and its peak-cutting and valley-filling effect is obvious, which can realize the cascade utilization in the microgrid. PV-ESM can consume the new energy well, realize the saving of electricity bills and the reduction of carbon dioxide emission. The overall cost of PV-ESM is expected to be recovered in the 11th year of operation. This paper can provide some reference values for the application of retired LiFePO4 batteries in microgrids.